Assessment of Microbial Contamination of Traditional Sweets in Yazd, Iran, in 2015 - hamidreza nasehinia; sajad rahimi; mehdi kiani; Mohammad Reza Ghaneapur; Fateme Ajam (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Diseases and poisonings, caused by the consumption of sweets contaminated with microorganisms, have always been considered as one of the major nutritional problems of people living in the developing countries, including Iran. Regarding this, the present study aimed to determine the prevalence of microbial contaminations of traditional sweets supplied in Yazd city, Iran, in 2015. Methods: This  cross-sectional study was conducted on 322 samples of traditional sweets supplied in Yazd confectionaries, which were randomly selected. These samples were tested in terms of such microorganisms as Enterobacteriaceae, Escherichia coli, yeasts, and molds, using the microbiological tests, which were based on the Iranian national standards.Results: According to the results, the prevalence rate of microbial contaminations was 33.8% (n=322). Furthermore, the “Pistachio Luz” and “Hajji Badam” had the highest (88.8%) and lowest (0%) prevalence rates of  microbial contamination, respectively. Additionally, the prevalence rate of contamination to Enterobacteriaceae, Escherichia coli, Molds, and Yeasts were 13.2%, 5%, 21.7%, and 11.4%, respectively. Conclusion: Given the high rate of microbial contamination in the traditional sweets, especially “Pistachio Luz”, offered in Yazd, more regulatory and monitoring measures should be taken in the production and distribution of these sweets.